Solid Lipid Nanoparticles: Preparation, Characterization and Applications- A Look Back - M. Swamivelmanickam; S. Sivakrishnan; R. Suresh (Challenges and Advances in Pharmaceutical Research Vol. 6, 2022)
Solid Lipid Nanoparticle [SLN] are numerous potential applications in the rapidly developing field of nanotechnology, including drug delivery, research and clinical medicine, and other diverse science and technology fields. Active pharmaceutical ingredients under development are often poorly water soluble and poorly bioavailable. SLN may be used to produce novel therapies because of their unique size-dependent characteristics. Traditional medication delivery technologies have certain limitations, and nanotechnology aims to eliminate such limitations. The therapeutic potential of solid lipid nanoparticles is intriguing. Preparation with lipids that can be tolerated by the body is their primary advantage. Nano-carriers that range in size from 10 to 1000 nanometres are known as Solid Lipid Nanoparticles. In an effort to overcome the shortcomings of polymeric nanoparticles, SLNs were introduced. A new formulation method was discovered by substituting lipids for polymers made from lipid nanoparticles. SLN in drug delivery examined in terms of potential advantages and disadvantages, as well as preparation methods and the principle behind drug release. SLNs in drug delivery are also characterised and applied. Nanometre-sized lipid particles are dispersed in water or surfactant solution in the form of "solid" or "liquid" lipids (SLNs). Hydrophilic and lipophilic drugs can now be delivered using SLN technology. The bioavailability of medications may also be improved with the use of SLNs. Adding drugs to nanocarriers provides a new method for delivering drugs to multiple levels of a patient’s body. As a result, solid lipid nanoparticles have piqued researchers’ interest due to their potential for delivering drugs in a regulated and targeted manner.